STATUS GIZI PADA PENDERITA TB PARUÂ DI PRIGEN KABUPATEN PASURUAN - Windartik, Emyk; Zakiyah, Ana (JURNAL KEPERAWATAN SEHAT, 2015)
AbstractNutritional status is one of the most important functions in the bodys defense against infection. Malnutrition in the circumstances, the immune response will be weakened so that the ability to defend it self against infection is lowered. This studed aims described the nutritional status of patients with pulmonary TB in Prigen Pasuruan. The method used is descriptive. The population was all patients with active pulmonary TB were 26 people that taken using the total sampling. This studed uses BMI calculation with the observed weight and height to determine the nutritional status of the patient. The results showed that the majority of patients with pulmonary TB have less nutritional status of as many as 17 people (65.4%). A person affected by pulmonary tuberculosis immune reaction will conduct an inflammatory reaction that disrupted the bodys metabolism which will result in weight is lowered, it is characterized by malaise because of the pain. In a state of malnutrition, weakened immune reaction so that the ability to maintain the infection is lowered, the presence of infectious disease can provide absorption barriers and obstacles intake of nutrients which the onset of malnutrition.Keywords:nutritional status, pulmonary TB patients